Komunikasi Kepala Satuan Paud Dalam Pengembangan Pendidikan Islam Melalui Pendekatan Teori Johari Windows (Studi Kasus Pada Paud Tunas Cendikia Binjai) - Budimansyah, Bambang Lestrika (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
The Johari Windows concept offers a deep understanding of how individuals perceive themselves and how these perceptions interact with other team members. Through the qualitative descriptive research method with purposive sampling, it is hoped that the results that will be achieved will objectively match the facts and data in the field without any engineering. Through analysis of this concept, it can provide insight into how to improve communication within work teams to achieve better performance. Good communication is communication that involves openness and mutual understanding between individuals. Knowing yourself is important, because there is an art to understanding your weaknesses and strengths. Meanwhile, the Johari Windows concept is based on internal and external communication patterns in Tunas Cendikia Binjai PAUD Principal, Internal Communication: (1) Open Quadrant, open information between staff, teachers and administration. (2) Hidden Quadrant: There may be some internal issues such as inter-staff conflict, worry or uncertainty. (3) Closed Quadrant: Some aspects of staff or teacher performance may be confidential to certain individuals, but known to management or fellow staff. (4) Unknown Quadrant: An individual's potential for developing new teaching methods, problem solving, or leadership skills that has not been fully explored or recognized. Meanwhile, External Communication: (1) Open Quadrant: Information shared with students' parents, community or other institutions. (2) Hidden Quadrant: There may be certain issues, such as student behavior problems or challenges in institutional management, that are not publicly disclosed but may be understood internally. (3) Closed Quadrant: The public face of the institution, such as an image or reputation that is carefully guarded, but there may be certain issues that are not revealed publicly. (4) Unknown Quadrant: Community expectations or needs that have not been fully accommodated by institutions..